Teachers' Perspectives and Practices on Effective Teaching Methods and Strategies at a Primary School in Prishtina - Jahiu, Edona (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractThis study examined and analyzed nine teachers' teaching practices with children in the sixth to seventh grades of primary school.   Effective teaching was discovered in this study to be dependent on three components of a classroom: 1) introduction – linking prior experience to the new issue; 2) sharing/discussing the primary topic; and 3) reflection/summarizing the lesson learned and new terms acquired. The findings indicated that students' learning and comprehension appeared to be contingent on the teacher's strategies for collaborating with students and constantly focusing their attention on the lesson (particularly on crucial features), which facilitated students' willingness to volunteer for discussion participation through open questions, constructive feedback, and so forth. Additionally, it provided teachers with insight on how to handle unforeseen classroom circumstances. For instance, numerous "attention-seeking" conflicts may arise, preventing the achievement of the objectives when time is spent on them. When reprimands and punishments are utilized, learners are reluctant to seek assistance or express their thoughts. Teachers must demonstrate their managerial competence by refraining to single out specific students in this situationAbstrakStudi ini meneliti dan menganalisis praktik mengajar sembilan guru dengan anak-anak di kelas enam hingga tujuh sekolah dasar. Pengajaran yang efektif ditemukan dalam penelitian ini bergantung pada tiga komponen ruang kelas: 1) pengantar – menghubungkan pengalaman sebelumnya dengan masalah baru; 2) berbagi/membahas topik utama; dan 3) refleksi/meringkas pembelajaran dan istilah-istilah baru yang diperoleh. Temuan menunjukkan bahwa pembelajaran dan pemahaman siswa tampaknya bergantung pada strategi guru untuk berkolaborasi dengan siswa dan terus-menerus memusatkan perhatian mereka pada pelajaran (terutama pada fitur-fitur penting), yang memfasilitasi kesediaan siswa untuk secara sukarela berpartisipasi dalam diskusi melalui pertanyaan terbuka, umpan balik yang membangun, dan sebagainya. Selain itu, ini memberi para guru wawasan tentang bagaimana menangani keadaan kelas yang tidak terduga. Misalnya, banyak konflik "mencari perhatian" mungkin muncul, mencegah pencapaian tujuan ketika waktu dihabiskan untuk itu. Ketika teguran dan hukuman digunakan, peserta didik enggan untuk mencari bantuan atau mengungkapkan pikiran mereka. Guru harus menunjukkan kompetensi manajerial mereka dengan menahan diri untuk memilih siswa tertentu dalam situasi ini.How to Cite: Jaihu, E. (2021). Teachers' Perspectives and Practices on Effective Teaching Methods and Strategies at a Primary School in Prishtina. TARBIYA: Journal of Education in Muslim Society, 8(1), 82-95. doi:10.15408/tjems.v8i1.20451.